Presence of anxiety and depression in gastroenterology outpatients in Metropolitan Lima - Saavedra Farach, Mariella (2023)
The objectives were to identify anxiety and depression in patients attending a gastroenterology outpatient clinic in the city of Lima, and to describe the gastroenterological history and symptoms most related to these disorders. 200 adult patients belonging to 32 districts of Metropolitan Lima attended from March to October 2021 were enrolled; the Hospital Anxiety and Depression Scale (HADS) adapted by Vilela was applied. The study was descriptive-correlational and prospective sample. 49% (n=98) reported anxiety, 19% (n=38) depression and 16.5% (n=33) both disorders concomitantly. Dyspepsia (v=0.216) and Irritable Bowel Syndrome (v=0.188) showed a statistical association for both variables. Diarrhea (v=0.214) and chest pain (v=0.215) were symptoms associated with anxiety, as well as chest pain with depression. Anxiety and depression are highly prevalent among patients that come to outpatient office visits, we suggest exploring these variables and offering a multidisciplinary approach to patients treated by this modality.